Study On Hygroscopicity And Sorption Of Oil Palm Trunk And Bamboo: Comparison Study With Rubberwood - Awalludin, Mohd Fahmi (2009)

(untitled)
A study on the hygroscopicity and sorption properties of non wood biomass of Elaeis guineensis trunk (oil palm) and bamboo culm of Gigantochloa schortechinii (Semantan bamboo) has been successfully done. Results obtained later were compared to the hygroscopicity and sorption properties of wood which was Hevea brasiliensis (rubberwood). Samples of 25-year-old oil palm trunk and 25-year-old rubberwood (Hevea brasiliensis) were provided by Central Kedah Plywood Factory Sdn. Bhd. in Kedah, Malaysia while samples of 6.5-year-old bamboo culm were taken from Nami Forest Reserved, Kedah Malaysia. Samples of oil palm trunk, bamboo culm and rubberwood has been left in RH chamber to undergo three cycles of fluctuated relative humidity until their moisture contents equilibrium with the subjected relative humidity. In the first cycle, samples undergo incremental relative humidity of 65% à 75% à 80% à 90%. It was then followed by a reduction of relative humidity; 90% à 75% à 65% à 50% à 30%. The final cycle is adsorption cycle with increasing relative humidity; 30% à 50% à 60%. The temperature of the relative humidity chamber was kept constant at 25°C. All three species samples give a sigmoid curve. Oil palm trunk and bamboo have an equal behavior to rubberwood in the context of relationship with surrounding humidity. On swelling studies, oil palm trunk did not show any significant difference between swelling in tangential and radial direction. Meanwhile, bamboo culm shows a significant result where tangential direction swells higher than radial direction. This behavior of bamboo culm seems to be same as rubberwood. Samples then were subjected to undergo compression strength test.